Educational aspirations of polish and Ukrainian youth: comparative analysis - Kviatkovskyi Mykhal (Borys Grinchenko Kyiv Metropolitan University, 2015)
The article presents the results of research educational aspirations of pupils in upper secondary schools in Poland and Ukraine. It is revealed similarities and differences between the two groups of results which could provide a starting point for further, wider and comprehensive research.